PEMBANGUNAN BERWAWASAN KEPENDUDUKAN KAJIAN ASPEK SOSIAL-EKONOMI-DEMOGRAFI PENDUDUK LANJUT USIA (LANSIA) DI SUMATERA SELATAN - Rosmiyati Chodijah Saleh (Jurnal Ekonomi Pembangunan, 2011)
The review was limited to the socio-economic-demographic aging of the population of South Sumatra, which in terms of differences in change between the District / City, which consist of 14 districts / cities. Being old is a natural process that can not be avoided. Preparing for the elderly population with a population of productive in terms of health and confidence. Investment of human resources emphasis should be encouraged and demographic variables need special attention. Changes in these demographic elements have broad impact on changes in population age structure in each region, which in turn can affect socio-economic circumstances and political area. Change in these demographic elements also have a profound effect on population age structure changes south of Sumatra, which in turn can affect socio-economic circumstance and political southern Sumatra.Keywords: Population-Based Development, the elderly population